2015
DOI: 10.1111/pai.12461
|View full text |Cite
|
Sign up to set email alerts
|

Food protein‐induced enterocolitis syndrome caused by fish and/or shellfish in Italy

Abstract: The chief peculiarities of acute fish and shellfish FPIES, compared to more frequent cow's milk or soy FPIES, are (i) later age of onset, (ii) longer persistence and (iii) possibility of tolerating fish other than the offending fish. Adverse reactions with shellfish are possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 19 publications
1
51
0
4
Order By: Relevance
“…The threshold dose could be a normal serving size or a very minute quantity, although it is thought that it is generally in the gram range [16, 17]. Sopo et al [8] did not find any differences in the severity of the symptoms developed after the first dose or after the whole serving was given, so they suggested that the quantity of fish ingested did not appear to be correlated with the severity of the symptoms presented. However, our results support the idea that the symptoms do correlate with the amount of fish ingested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The threshold dose could be a normal serving size or a very minute quantity, although it is thought that it is generally in the gram range [16, 17]. Sopo et al [8] did not find any differences in the severity of the symptoms developed after the first dose or after the whole serving was given, so they suggested that the quantity of fish ingested did not appear to be correlated with the severity of the symptoms presented. However, our results support the idea that the symptoms do correlate with the amount of fish ingested.…”
Section: Discussionmentioning
confidence: 99%
“…The OFC is not risk free and many patients develop severe symptoms after this procedure. There is no generally accepted protocol to perform the OFC, and several ways to do it have been described [4, 7, 8]. The International Consensus Guidelines for the Diagnosis and Management of Food Protein-Induced Enterocolitis Syndrome recommends administering the challenging food at a dose of 0.06–0.6 g, usually 0.3 g of the food protein per kilogram of body weight, in 3 equal doses over 30 min.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of a series of infants with food protein-induced enterocolitis by Sicherer et al [11] (16 patients) and Burks et al [12] (43 patients) further characterized clinical features and refined food challenge protocols. More recent reports have identified various solid foods as triggers for FPIES [13][14][15][16][17][18]. Prior to implementation of the International Classification of Diseases, Tenth Revision (ICD-10) code for FPIES (K52.2) in October 2015, no uniform ICD code existed [19].…”
Section: Historical Perspectivementioning
confidence: 99%
“…FPIES caused by finned fish (eg, codfish, salmon, tuna) has been described as one of the most common triggers in infants and toddlers in Spain and Italy, likely reflecting the importance of fish in the diet and the relatively earlier age of introduction compared with other countries [14][15][16][39][40][41][42][43][44]. Table 2 presents the characteristics of fish-induced FPIES.…”
Section: Fpies Caused By Fishmentioning
confidence: 99%
“…Solid-food FPIES tends to start later than cow’s milk and soy FPIES, perhaps because solids are introduced later at around 6 months of age [10]. In an Italian study, the chief peculiarities of acute fish and shellfish FPIES [19], compared to more frequent cow’s milk or soy FPIES, were an older age of onset, longer persistence, possibility of tolerating fish other than the offending fish, and adverse reactions to shellfish.…”
Section: Food Protein-induced Enterocolitis Syndromementioning
confidence: 99%